Conservative management a safer option in high-grade renal injuries: Our institutional experience - Ponnusamy, Periasamy; Poovathai, Senthilkumar; Rajkumar Ramakrishnan; Sangreshi, Vinayak (Asian Journal of Medical Sciences, 2023)
Background: Renal injuries constitute around 1–5% of all trauma associated injuries. In present era, there has been a focus toward conservative management for blunt renal injuries. Advancement in radiographic injury grading, improved hemodynamic monitoring systems, valid renal injury grading systems allows successful non-operative management for renal preservation even in cases of Grades IV and V. Aims and Objectives: The aim of our study was to assess outcomes of patients managed conservatively (non-operatively) for high-grade blunt renal injury at our center. The objective of this study is to assess whether high-grade renal injuries can be managed by conservative management successfully or not. Materials and Methods: The study conducted in a retrospective manner using hospital records of the past 2 years. Thirty patients with blunt renal injuries were included in the study and were categorized based on the American association for the surgery of trauma (2018 revised) injury grading. These management strategies were analyzed in terms of “failure of conservative management,” complications, and need for adjuvant procedures. Statistical data analysis was done using Microsoft Excel (2019) software. Results: Thirty patients were included in the study with a mean age of years. Out of the total 30 patients, 17 had Grade I–III injuries, and 13 had Grade IV. All the Grade I–III patients were managed conservatively and required no adjunctive procedures. 10 out of 13 cases of Grade IV injuries underwent non-operative management. Complications included urinary tract infection (5), persistent hematuria (3), hypertension (1), urinoma (2), and ileus (1). All complications were of Clavien Dindo classification of grade 1–2. Conclusion: Grade IV blunt renal injuries can be managed conservatively if the patient is hemodynamically stable.